Preparing students to apply transversal skills - a case study in higher education - Belchior-Rocha, H.; Almeida, F.; Casquilho-Martins, I.; Ferreira, J. (Edulearn17 Proceedings – 9th International Conference on Education and New Learning Technologies, 2017)
With the implementation of the Bologna Process in higher education, competences are the central axis of the teaching / learning process, both in the technical-professional dimension and in the perspective of transversely. Although the concept of transversal competence does not generate consensus, one of the main purposes of the current education and learning efforts is to equip students with competences that are transferable across contexts and that lie beyond approaches to content or areas of knowledge. The purpose of this ongoing research is to devise a profile of transversal skills of the education professional, able to guide the training work in the higher education institutions, support the tasks of evaluation and certification of the said competences and promote the personal and professional development of 1st cycle students, where the implementation of the transversal laboratory in Portuguese University will be analysed as a case study, comparing performance indicators and forms of adherence to students' transfer of competences. Exercising this role is only possible if the teacher is a reflexive professional, an agent of his own formation and a stimulator of the student's formation, mediating the construction of knowledge with playful, reflexive, challenging and creative activities, enabling students to become participant subjects , autonomous and critical.